PENGARUH BRAND IMAGE, KUALITAS PRODUK, PERSEPSI HARGA, GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN - Andhika Nur Mustofa; Wiyadi Wiyadi (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
A company is required to provide products with good quality and according to consumer needs, therefore companies must develop and produce the best products so that the products offered in the market sell well. The aim of this study is to examine the impact of consumers' lifestyles on their opinions about smartphone costs, brand image, and product quality. Students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta participated in this study. In illustrating the findings, this study used data from 100 participants, all of whom met certain criteria. The SPSS 26 analysis tool was used to process the questionnaire used for data collection. The findings prove that (1) brand image substantially influences purchasing decisions. 2) product quality significantly influences purchasing decisions. 3) price perceptions do not substantially influence purchasing decisions. 4) A person's way of life has a large impact on what they believe. Keywords: brand image, price, lifestyle